Happiness and positive psychology - McHugh, Sandie; Carson, Jerome (Positive psychology in practice, 2025)
Positive Psychology is a swiftly expanding field, attracting academics who commit their careers to its advancement. Although happiness was initially a focal point in Positive Psychology research, some academic circles now prefer the more precise concept of flourishing. Without doubt, the primary goal of Positive Psychology is to enhance flourishing, even though the term happiness holds broader significance through history and across cultures. This work is the first to look at happiness as a crucial aspect of Positive Psychology. Authors Sandie McHugh and Jerome Carson begin by introducing definitions of happiness and Positive Psychology, followed by a discussion on the measurement of happiness. The study then navigates through the historical evolution of these concepts, exploring the transition from Humanistic Psychology to Positive Psychology and the shift from happiness to flourishing. Chapters explore the global perspective on happiness, focusing on enhancing happiness through individual and external interventions. It concludes by contemplating the future of happiness and Positive Psychology, summarizing self-help interventions and reflecting on the lessons learned throughout the exploration. Happiness and Positive Psychology is essential reading for academic professionals in Positive Psychology seeking theoretical insights and for students in Positive Psychology programs looking for foundational knowledge and practical insights. Psychologists specializing in well-being and flourishing, researchers in humanistic psychology, and practitioners in applied positive psychology, such as therapists and counsellors, benefit from real-world case studies presented throughout the work.